Abnormal Functional Network Centrality and Causal Connectivity in Migraine Without Aura: A Resting‐State fMRI Study - Di Zhang; Liyan Lu; Xiaobin Huang; Xiaojing Zhao; Yamei Zhang; Tong Fu; Fengfang Li; Xinying Wu (Brain and Behavior)
ABSTRACT Objective The pathophysiological mechanism of migraine is still not clear. Thus, this study aimed to evaluate the changes in effective connectivity (EC) in the brain functional network underlying migraine and its association with clinical measures of migraine. Background Fifty patients with episodic migraine without aura (MwoA) and 48 healthy controls (HCs) were enrolled in this study. Spontaneous activity in the brain was evaluated using the degree centrality (DC) method, and the brain regions with obvious signal differences between the two groups were taken as seed points for whole brain Granger causality analysis (GCA) analysis. The values of the brain regions with differences in DC and GCA were extracted and correlated with clinical measures of migraine. Results Compared to the HCs, the MwoA patients showed decreased DC in the left inferior temporal gyrus (ITG) and increased DC in the right precuneus and exhibited significantly decreased EC from the left ITG to the left inferior parietal gyrus and right inferior occipital gyrus (IOG) as well as significantly increased EC from the left postcentral gyrus and left cerebellum posterior lobe to the left ITG. Moreover, decreased EC from the left thalamus to the right precuneus was found in the MwoA patients compared to the HCs. The DC values in the right precuneus were significantly negatively correlated with the duration of headache. Additionally, we found a significantly positive correlation between the Migraine Disability Assessment questionnaire score and the EC from the left ITG to the right IOG, as well as between the intensity of headache and the EC from the left thalamus to the right precuneus. Conclusions This study found changes in the EC of the brain functional network underlying migraine and their associations with migraine‐related parameters. These findings are helpful for understanding the pathophysiological mechanism in migraine patients.